Ecological response of Casuarina equisetifolia to environmental stress in coastal dunes in China. Issue 3 (4th May 2018) - Chen, Dezhi; Ye, Gongfu; Gao, Wei; You, Longhui; Nie, Sen; Wang, Ya Ping
ABSTRACT: Seasonal variations in Casuarina equisetifolia branchlet diameter, branchlet internode length, and branchlet length were investigated in plants at various distances from the coast in a Casuarina forest, using field studies and laboratory analysis. The branchlet traits of C. equisetifolia exhibited approximately linear change with increasing distance from the coast: the branchlet diameter became thinner, while the internode and branchlet lengths became longer. The change in branchlet traits was most evident at 0–20 m from the coast. There was little change in the distance from 40 m to 80 m. The branchlets on trees in favorable habitats showed an increase in internode length and reduced diameter, whereas the branchlets in unfavorable habitats had reduced internode length but increased diameter in limited branchlet length. The spatial changes in C. equisetifolia branchlet traits appear to be an adaptation to the environment, in response to the effects of blown sand in the coastal front area. The results suggest that to maintain growth this species shows marked adaptability to the effect of blown sand.